PENGARUH MATERIAL LOKAL KEDIRI TERHADAP TINGKAT DURABILITAS LAPIS STRUKTUR JALAN - Achmad Khabib Kurnia; Andri Dwi Cahyono; Imam Mustofa; Evita Fitrianis Hidiyati; Ricco Dwi Yuliawan; Tantra Tegar Permady; Achmad Fikri Haikal; Dwi Nur Khayatin; Audy Yoga Pratama (Jurnal Riset Rekayasa Sipil, 2023)
Air conditioning or asphalt concrete is formed from coarse aggregate, fine aggregate, and asphalt. An aggregate is a collection of grains of crushed stone, gravel, sand, and other minerals in the form of both natural and artificial products. Coarse aggregate is sieve holder No. 8 (2.36 mm) retained aggregate while fine aggregate is sieve No. 8 (2.36 mm) passed aggregate. The problems that often occur in road pavement layers are poor durability and surfaces that are easy to wear out. This study aimed to find the maximum marshall value in the form of 60/70 penetration asphalt mixture stability. This study used an experimental method with a laston AC-BC test, the test was carried out with abrasion, gradation, specific gravity, and Marshal testing tests using marshal test equipment, following SNI 06-2489-1991, or AASHTO T245-90, or ASTM D1559-76. Using aggregates from the Kedak area, stability results of 3046, 4896, 3754 were obtained, which met the standards of the Bina Marga specifications standards. So that the aggregate from the Kedak area can be used as an alternative constituent material in road planning in the Kediri area because it is more efficient and has good durability.